Implementation of clinical nursing supervision with the proctor and reflective models: literature review - Prihandhani, I Gusti Agung Ayu Sherlyna; Wulanyani, Ni Made Swasti; Wirawan, I Made Ady (International Journal of Public Health Science (IJPHS), 2024)
Nursing supervision can impact nurses' ability to generate, direct, and maintain behaviors relevant to nurses’ work environment. However, the fact is that oversight has not been implemented optimally. The following are the sample inclusion criteria in this research article: i) Research articles published between 2018 and 2023. ii) The article's research design is experimental or publication. iii) Research studies examine how the process of establishing vision supervision is carried out. iv) The research article is about clinical nurse supervision. A systematic review was performed in this study to assess 12 journals that were studied and included in the inclusion criteria. The findings of this investigation were achieved. The framework and clinical supervisor’s perceptions are divided into three themes: organizing learning, supporting tool for understanding what nursing care is, and developing own supervision practice. Supervisors view the fundamentals of care framework favorably and utilize it to structure and stimulate students' contemplation on what nursing is and demands.